(untitled) (International Journal of Occupational Safety and Health, 2025)
Introduction: Regional musculoskeletal disorders (MSDs) are prevalent in the textile industry, primarily due to repetitive or static work postures. This study aimed to assess whether specific muscle group stretching exercises could reduce MSDs complaints among workers in the textile industry. Methods: A quasi-experimental design with a pretest–posttest approach without a control group, which limits causal inference, was employed. Thirty textile workers participated in a structured stretching program twice daily for 8 weeks. Complaints of MSDs were assessed using the Nordic Body Map (NBM) questionnaire at baseline, Week 4, and Week 8. The data were analyzed using Repeated Measure ANCOVA to control for age, gender, length of employment, and BMI, with effect sizes calculated using Cohen’s d. Results: Significant reductions in MSDs complaints were observed across seven body regions (p<0.05). The largest improvement was in the upper neck region (mean score reduction = 0.83; Cohen’s d = 1.116), indicating a very large effect size. Covariates (age, gender, length of employment, and BMI) did not significantly influence outcomes (p > 0.05). Conclusion: While targeted stretching of specific muscle groups appeared to reduce regional MSDs among textile workers, the absence of a control group limits the ability to draw definitive causal conclusions. Future studies should employ randomized controlled trials with larger sample sizes to confirm these preliminary findings.